Different natures of surface electronic transitions of carbon nanoparticles. Issue 34 (16th August 2017) - Sciortino, A.; Cayuela, A.; Soriano, M. L.; Gelardi, F. M.; Cannas, M.; Valcárcel, M.; Messina, F.
Abstract : Pictorial representation of the fluorescence mechanisms proposed for carbon nanodots. Blue: tunable visible emission from surface-delocalized electronic states. Violet: UV emission from localized, quasi-molecular chromophores. Abstract : The photoluminescence behaviour of carbon-based nanodots is still debated. Both core and surface structures are involved in the emission mechanism, and the electronic transitions can be modified by external agents such as metal ions or pH, but the general relation between the structure and the optical function is poorly understood. Here, we report a comparative study on the effects of these variables, changing the core structure from crystalline to amorphous, and modifying the surface structure by different passivation procedures. Our results highlight that the emission mechanism of the tunable visible fluorescence is identical for crystalline and amorphous samples, indicating the independence of the emission from the core structure. Furthermore, surface functionalization weakly influences the emission peak position, but has large consequences on their interaction with different metal ions. This suggests the involvement of quasi-degenerate electronic states originating from the high density of different interacting groups on the surface. Finally, we report the presence of an unusual ultraviolet emission band for the amorphous sample, likely involving localized molecular-type chromophores with carboxyl ends. Our findings provide new information on the emission mechanisms of CDs and can be used to engineer sub-types of CDs displaying very similar emission features, but specifically tailored for different sensing applications.